2013
DOI: 10.21109/kesmas.v7i7.31
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Penyakit Stroke

Abstract: AbstrakPenyakit stroke merupakan penyebab kematian dan kecacatan kronik yang paling tinggi pada kelompok umur diatas usia 45 tahun terbanyak di Indonesia. Tujuan penelitian ini untuk mengidentifikasi determinan utama yang berhubungan dengan penyakit stroke pada masyarakat di kelurahan Kebon Kalapa Bogor. Analisis lanjut terhadap 1.912 responden subset baseline data penelitian "Studi Kohort Faktor Risiko Penyakit Tidak Menular" Data dikumpulkan dengan metode wawancara pada penduduk tetap di kelurahan Kebon Kala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
1
5
2
6
Order By: Relevance
“…The results of this study are similar with a baseline subset data analysis study conducted in Bogor, West Java which found that the lack of physical activity was not a risk factor for stroke compared with those with sufficient physical activity. 25 In contrast, our results were not consistent with the results of data analysis on The 2013 Indonesia Basic Health Research (Riskesdas) 26 which stated that respondents with less physical activity showed a higher prevalence of stroke compared with those who did enough physical activity. In addition, study in India also stated that physical activity is a risk factor for stroke.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study are similar with a baseline subset data analysis study conducted in Bogor, West Java which found that the lack of physical activity was not a risk factor for stroke compared with those with sufficient physical activity. 25 In contrast, our results were not consistent with the results of data analysis on The 2013 Indonesia Basic Health Research (Riskesdas) 26 which stated that respondents with less physical activity showed a higher prevalence of stroke compared with those who did enough physical activity. In addition, study in India also stated that physical activity is a risk factor for stroke.…”
Section: Discussioncontrasting
confidence: 99%
“…Di Indonesia, penyakit ini merupakan salah satu penyebab kematian dan kecacatan neurologis yang tertinggi. Diperkirakan setiap tahun 500.000 penduduk yang terkena serangan stroke, ada sekitar 2,5% atau 125.000 orang yang meninggal, selebihnya mengalami cacat ringan maupun berat (Riyadina dan Rahajeng, 2013).…”
Section: Pendahuluanunclassified
“…Setengah dari pasien pasca stroke akan merasakan gejala sisa serangan stroke yang sangat beragam, yakni gangguan gerak atau pun motorik, gangguan penglihatan, gangguan bicara, perubahan emosi, serta gejala lain sesuai lokasi otak yang mengalami penyumbatan (Misbach et al, 2014). Menurut penelitian (Riyadina, 2013) mengatakan bahwa masyarakat yang menderita hipertensi berisiko 4 kali lebih besar untuk mengalami penyakit stroke (OR = 4,20; CI 95% = 2,20 -8,03. Setengah dari pasien pasca stroke juga akan mendapatkan gejala sisa penyakit stroke yang beragam, misalkan gangguan gerak atau motorik, gangguan penglihatan, gangguan bicara, perubahan emosi, serta gejala lain sesuai lokasi otak yang mengalami penyumbatan (Misbach et al, 2014).…”
Section: Pendahuluanunclassified